Occurrence and characterization of food-borne pathogens isolated from fruit, vegetables and sprouts retailed in the Czech Republic - Vojkovská, Hana; Myšková, Petra; Gelbíčová, Tereza; Skočková, Alena; Koláčková, Ivana; Karpíšková, Renáta (Food microbiology, 2017)
Food of non-animal origin is a major component of the human diet and has been considered to pose a low risk from the point of view of bacteriological safety. However, an increase in the number of outbreaks of illness caused by such pathogens and linked to the consumption of fresh fruit and vegetables have been reported from around the world recently. Salmonella spp., STEC (Shiga toxin producing Escherichia coli) and Listeria monocytogenes are among the most frequently identified agents. Additionally, the transmission of antibiotic resistant strains including also the methicillin resistant S. aureus (MRSA) to humans via the food chain is one of the greatest public health problems being confronted today. Therefore, we focused on the bacterial safety of fruit, vegetables and sprouts on sale in the Czech Republic. One strain (0.3%) of Salmonella Enteritidis phage type PT8, one strain (0.3%) of MRSA and 17 strains (5.0%) of L. monocytogenes were isolated from a total of 339 collected samples. The most problematic commodities were frozen fruit and vegetables (packed and unpacked) and fresh-cut vegetables. Our findings indicate deficiencies in hygiene practices during harvesting, processing and distribution of these commodities. Although sprouts and berries are the most likely to be contaminated by human pathogens, only two samples were positive for the presence of L. monocytogenes.
Keywords: Salmonella; Humans; STEC; semenáček; Salmonella enteritidis; Foodborne; Listeria monocytogenes; Methicillin-Resistant Staphylococcus aureus; lidé; Colony Count, Microbial; shiga-toxigenní Escherichia coli; Vegetables; zelenina; Food Microbiology; Shiga-Toxigenic Escherichia coli; Escherichia coli O157; MRSA; methicilin rezistentní Staphylococcus aureus; Seedlings; počet mikrobiálních kolonií; polymerázová řetězová reakce; Czech Republic; Polymerase Chain Reaction; ovoce; Bacterial Typing Techniques; Food Safety; Fruit; Bacteria; bezpečnost potravin; Česká republika; techniky typizace bakterií; potravinářská mikrobiologie